Comprehensive Research in Earthquake Forecasting and Seismic Hazard Assessment (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint "Comprehensive Research in Earthquake Forecasting and Seismic Hazard Assessment" is a collection of articles dealing with various aspects of the physics of seismic processes, earthquake forecasting, and the search for their precursors. All published articles can be roughly divided into three unequal groups according to the number of articles presented. The first group includes theoretical and methodological articles. The second group includes articles confirming one or another model of seismicity behaviour in anticipation of a strong earthquake. Finally, the third and most numerous group of articles consists of those analysing the results of long-term observations of the behaviour of various geophysical fields. We are confident that each of these articles will find an interested reader, and that the collection as a whole deserves the attention of representatives of the scientific community concerned with the problem of earthquake forecasting and the search for their precursors.